Gravity - West, Melissa 1980-; Burford, Michelle (The Taking, 2012)
In the future, only one rule will matter: Don't. Ever. Peek. Seventeen-year-old Ari Alexander just broke that rule and saw the last person she expected hovering above her bed - arrogant Jackson Locke, the most popular boy in her school. She expects instant execution or some kind of freak alien punishment, but instead, Jackson issues a challenge: help him, or everyone on Earth will die. Ari knows she should report him, but everything about Jackson makes her question what she's been taught about his kind. And against her instincts, she's falling for him.